胃がん診断用のマイクロＲＮＡバイオマーカー (2025)
Disclosed are methods of determining the likelihood of a subject having or developing a gastric cancer. The methods comprise measuring the expression level of at least one miRNA having at least 90% sequence identity with an miRNA as described herein in a non-cellular biofluid sample obtained from the subject, wherein differential expression of miRNA expression in the sample obtained from the subject, as compared to a control, may be indicative of the subject having gastric cancer and wherein the miRNA may be either an miRNA listed as "up-regulated" or an miRNA listed as "down-regulated". Also disclosed is a method of determining the likelihood of a subject having or developing a stage of a gastric cancer.